Study on properties of ybco superconductor with addition titanium oxideTiO2 by solid state reaction - Ezzarudin Eezahan (2017)
In this study, the effects of TiO2 addition on YBCO superconductor were studied. TiO2 was added into YBCO superconductor samples with 1%, 2% and 3% weight percentage addition respectively were prepared using the conventional solid-state reaction method. The oxide has a triple perovskite-type structure and it also be a first superconductor that have critical temperature. Characterization of sample was performed by X-ray Diffraction (XRD), X-ray Fluorescence (XRF) and measurement the resistivity of superconductor. Using XRD method, the crystal structure and related parameter of compound in YBCO with addition was determined. YBCO sample has the orthorhombic structure and TiO2 as addition not destroy the structure of YBCO system. The intensity peak was increased with increasing the addition. In XRF the metal element in pure YBCO and with addition was analyzed. The elemental analysis was traced is high percentage concentration of Barium Oxide at all samples. For resistivity measurement, the YBCO superconductor ceramic has properties are zero resistivity. The resistivity was decreased by increasing the addition of TiO2. In conclusion, the YBCO with addition TiO2 superconductor improves the superconducting performance of YBCO superconductor.